Selected Letters between James Beattie and Elizabeth Montagu (1758–ca. 1799), University of Aberdeen - Caroline Franklin (Huntington Library Quarterly, 2018)
This online sample edition of letters to James Beattie accompanies and illustrates the 2018 HLQ journal article 'An Honourable alliance'.